OCEAN CHANGE AND CLIMATE CHANGE - TWO DIMENSIONS OF A PROBLEM - Hoi, Nguyen Chu (Vietnam Journal of Marine Science and Technology, 2015)
The world ocean, including oceans and marginal seas, covers 71% of the Earth’s area and has been considered as a supportive system to the Earth’s life. Especially, the ocean maintains food and energy security for humankind while such sources are being exhausted on the mainlands. The climate change and its impacts on oceans, coasts and islands have been know more than ocean change and its impacts on climate system. The scientists have continuously affirmed that climate change and ocean change are closely related and are considered as two dimensions of the same problem. The paper presents the ocean change, the role of the ocean in adapting to the impacts of the climate change and the approaches to respond to the changes worldwide and in Vietnam.